ASSESSMENT OF REQUEST PATTERN AND UTILITY OF RHEUMATOID FACTOR IN A TERTIARY HOSPITAL IN NORTH EAST NIGERIA - Dabkana TM; Yerima A; Nyaku FT; Ajayi BB; Stanley BT; Ali MR (Ntec Specialist, 2019)
Background: The diagnostic utility of Rheumatoid Factor (RF) test is not well documented. The question therefore is: 'when is it appropriate to make this request'? When patients' own immunological defense mechanisms go awry and start attacking one's tissues, (autoimmune), there usually arises a problem. This usually affects the heart, musculoskeletal system and other organs giving rise to signs and symptoms that are seen in other ailments. The joints are the most common site of affectation and an early diagnosis may go a long way in managing the disease. Usually an antibody (Rheumatoid factor) is found in such patients. It is formed against the Fc portion of IgG, forming an IgG-Fc immune complex that normally leads to the disease process. It is this complex (usually an IgM) in the patient's serum that is exposed to a commercial antigen in the laboratory and the titer determined against a standard. The normal level is usually less than 14IU/ml. Levels higher are usually considered abnormally high, elevated or positive. A negative RF test however does not mean that the patient hasn't got the disease. Objective: To determine the frequency of positivity of rheumatoid factor and the context in which the requests are made by group of physicians and advise on when to make the request. Methods: A retrospective study of case notes of 354 patients requested to perform rheumatoid factor test at the immunology department over a period of 6 years were reviewed. The requesting departments, clinical and demographic characteristics of patients were reviewed and analyzed. Data analyzed using SPSS version 22. Results: Of the 354 requests made, 265 (74.9%) were due to musculoskeletal symptoms and 20 (5.6%) were positive for RF. Of the 20, 19 (95%) had polyarthritis while 1 (5%) was asymptomatic. The mean age was 37.06±13.91 and 205 (57.9%) were females. Most (137 or 38.7%) of requests for RF were from the general out-patient department and 108 (30.5%) from medical out-patient department. The sensitivity and specificity for RF test in detecting MSK disease were 7.17% (95%CI, 4.37-10.97) and 98.88% (95%CI, 93.90-99.97). The positive likelihood ratio was 6.38% (95% CI, 0.87-40.99). The positive predictive value (PPV) and negative predictive value (NPV) were 95.0% (95%CI, 77.02-99.29) and 26.35% (95%CI, 25.48-35.30). Test accuracy was 30.23% (95% CI, 25.48-35.30). Conclusion: We recommend that rheumatoid factor should be requested only in patients with fleeting arthritis, good clinical evaluation for signs and symptoms and looking for differentials